The Impact of Leadership Styles on Employee Performance in Public Universities in Kenya: A Case Study of Multimedia University of Kenya - Ogambi, Macdonald Ouko; Kijana, Eunice; Kigatiira, Kinya (International Journal of Research in Interdisciplinary Studies, 2024)
This study explored the impact of leadership styles on employee performance at Multimedia University of Kenya (MMU) using William Ouchi’s Theory Z. A descriptive survey design was used and primary data was collected from non-teaching and academic staff across various departments using questionnaires and interviews. Stratified sampling was used to select 194 respondents including 8 department heads who provided expert opinions. Findings showed that MMU’s culture of innovation, quality and teamwork was found to be shaped by leadership which greatly influences employee attitudes and performance. Also streamlined work processes correlated positively with task completion, adherence to quality standards and job satisfaction. The study recommends investing in leadership development programmes to enhance communication, foster collaboration and align leader-ship philosophy with organisational culture to positively impact the organisational environment.